1999
DOI: 10.1029/1999wr900189
|View full text |Cite
|
Sign up to set email alerts
|

Submarine groundwater discharge and associated chemical input to a coastal sea

Abstract: Abstract. This paper presents a theoretical model of flow and chemical transport processes in subterranean estuaries (unconfined brackish groundwater aquifers at the ocean-land interface). The model shows that groundwater circulation and oscillating flow, caused by wave setup and tide, may constitute up to 96% of submarine groundwater discharge (SGWD) compared with 4% due to the net groundwater discharge. While these local flow processes do not change the total amount of land-derived chemical input to the ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
295
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(312 citation statements)
references
References 11 publications
12
295
2
Order By: Relevance
“…While wave periods typically range from a few to tens of seconds in the nearshore zone, wave height also varies over long time scales with intensified wave conditions occurring, for 19 instance, in response to offshore storms. Waves drive large volumes of water exchange across the CUA-ocean interface [Li et al, 1999]. It is challenging to quantify wave-driven recirculation from field data alone, but estimates have been provided through numerical studies [e.g., Xin et al, 2010;Bakhtyar et al, 2011;Geng et al, 2014;Robinson et al, 2014;Xin et al, 2014].…”
Section: Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…While wave periods typically range from a few to tens of seconds in the nearshore zone, wave height also varies over long time scales with intensified wave conditions occurring, for 19 instance, in response to offshore storms. Waves drive large volumes of water exchange across the CUA-ocean interface [Li et al, 1999]. It is challenging to quantify wave-driven recirculation from field data alone, but estimates have been provided through numerical studies [e.g., Xin et al, 2010;Bakhtyar et al, 2011;Geng et al, 2014;Robinson et al, 2014;Xin et al, 2014].…”
Section: Wavesmentioning
confidence: 99%
“…Field and numerical studies quantified the tidal effect on SGD and showed that tide-induced recirculation can represent a major portion of total SGD [e.g., Li et al, 1999;Taniguchi, 2002;Robinson et al, 2007c;Li et al, 2009]. Seawater infiltration into an aquifer occurs on the rising tide and exfiltration (saline SGD) on the ebbing tide [Robinson et al, 1998;Sholkovitz et al, 2003;Robinson et al, 2007c].…”
Section: Tidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Time-averaging of the beach groundwater response to wave forcing reveals a localized seaward directed circulation cell [Longuet-Higgins, 1983; which has implications for the availability and quality of coastal groundwater resources and for the fate of contaminants [e.g., Li et al, 1999;Moore, 1999]. The dynamics of the water table exit point on the beach face have also been linked to the distribution of interstitial macrofauna [e.g., McArdle and McLachlan, 1991] and to aeolian sediment transport on beaches [e.g., Jackson and Nordstrom, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…For example, seawater circulates through a coastal aquifer under the force of gravity (Li et al, 1999;Li and Jiao, 2003), from oceanic forces such as waves and tides (Taniguchi et al, 2002;Burnett et al, 2003), as a result of dispersive circulation along the freshwater-saltwater boundary within the aquifer (Kohout, 1960), and from changes in upland recharge (Michael et al, 2005).…”
Section: Groundwater Flow At the Coastmentioning
confidence: 99%